An atypical presentation of cutaneous myiasis of the scalp in North Punjab: a case report - Mohsin, Amber; Riaz, Jibran Nadeem; Nabi, Haroon (Journal of the Pakistan Medical Association, 2023)
Myiasis is an ectoparasitic infestation caused by larvae of arthropods in the group Diptera. Cutaneous myiasis is the infection of skin and includes the following types: furuncular, migratory and wound myiasis. Out of all the organisms responsible for this disease, Wohlfahrtia vigil is the most common causative agent in Pakistan, usually seen from June to September with nearly all presentations occurring at a young age. In our case, a patient without a history of trauma, skin erosion or animal exposure has a unique presentation of cutaneous myiasis. Here, an effort was made to treat a 15-year-old otherwise healthy female with a multisegmented treatment modality. A follow up visit was conducted every three days for three months at the end of which a 60% decrease in the size of the open wound was observed. Keywords: Myiasis, ulcer, Pakistan.